Modulation of the Lipid Profile of Reconstructed Skin Substitutes after Essential Fatty Acid Supplementation Affects Testosterone Permeability - Mélissa Simard; Pierre Julien; Julie Fradette; Roxane Pouliot (Cells, 2019)
Skin models with efficient skin barrier function are required for percutaneous absorption studies. The contribution of media supplementation with n-3 and n-6 polyunsaturated fatty acids (PUFAs) to the development of the skin barrier function of in vitro skin models remains incompletely understood. To investigate whether PUFAs, alpha-linolenic acid (ALA, n-3 PUFA) and linoleic acid (LA, n-6 PUFA), could enhance the impermeability of a three-dimensional reconstructed human skin model, skin substitutes were produced according to the self-assembly method using culture media supplemented with either 10 μM ALA or 10 μM LA. The impact of PUFAs on skin permeability was studied by using a Franz cell diffusion system to assess the percutaneous absorption of testosterone and benzoic acid. Our findings showed that ALA supplementation induced a decrease in the absorption of testosterone, while LA supplementation did not significantly influence the penetration of testosterone and benzoic acid under present experimental conditions. Both ALA and LA were incorporated into phospholipids of the skin substitutes, resulting in an increase in n-3 total PUFAs or n-6 total PUFAs. Collectively, these results revealed the under-estimated impact of n-3 PUFA supplementation as well as the importance of the n-6 to n-3 ratio on the formation of the skin barrier of in vitro reconstructed human skin models.